Analysis of reinforced concrete beams strengthened using concrete jackets. (1st February 2017) - Alhadid, M. Monir A.; Youssef, Maged A.
Highlights: A method is developed to consider the influence of slip in jacketed RC beams. Flexural behavior of the jacketed beams is examined in view of a parametric study. Interfacial slip and shear stress distributions are determined in the analysis. Modification factors are proposed to adjust the monolithic load-deflection curves. Abstract: Analysis of jacketed Reinforced Concrete (RC) beams considering the interfacial slip effect is a complicated problem. In the current practice, slip is neglected in the analysis and monolithic behavior is assumed in the jacketed section resulting in higher estimates of stiffness and/or capacity. Engineers need simplified yet robust tools to predict the actual behavior of jacketed RC beams. This paper provides a simplified method to analyze jacketed RC beams taking into account the interfacial slip distribution and the actual nonlinear behavior of both concrete and steel. An iterative calculation algorithm is developed to determine the moment-curvature and load-deflection curves of the jacketed beams. The developed method provides an evaluation of the slip and shear stress distributions, which allow assessing the influence of surface roughness conditions. The developed method is utilized to conduct an extensive parametric study, which resulted into modification factors to calculate the capacity and deformations of strengthened beams while accounting for interfacial slip.